Classification of Covid-19 Diseases Through Lung CT-Scan Image Using the ResNet-50 Architecture - Lucky Indra Kesuma; Rudiansyah Rudiansyah (Universitas Sriwijaya, 2023)
Covid-19 is a respiratory tract disease caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The Covid-19 disease was first reported in Wuhan, China, in December 2019. The SARS-CoV-2 virus is primarily transmitted through human contact, and the World Health Organization has proclaimed a global pandemic (WHO). Symptoms of Covid-19 can range from asymptomatic to mild and severe. One way to diagnose Covid-19 disease can be done by examining lung abnormalities on the results of a Computed Tomography Scan (CT-Scan) of the lungs. However, determining the diagnostic results requires high accuracy and a long time. For this reason, an automated system is needed to make it easier for medical personnel to diagnose Covid-19 disease quickly and accurately. One of the automated systems with computer assistance in detecting abnormalities in CT-Scan images of the lungs is to perform pattern recognition